Youth Perspectives on the Recommended Age of Mobile Phone Adoption: Survey Study - Aliah Richter; Victoria Adkins; Ellen Selkie (JMIR Publications, 2022)
BackgroundDespite increasing prevalence of phone ownership in early adolescence, there is a deficit of evidence-based guidance on the appropriate time to provide youth their first phone. ObjectiveThis survey study explored age recommendations for phone ownership among a diverse panel of youths, as their experiences are an important contribution to the development of ownership guidelines. MethodsParticipants were recruited from MyVoice, a national panel of over 765 youth (14 to 24 years old) who respond to weekly SMS text message-based surveys. Questions were distributed between January 24 2018, and March 20, 2018. Inductive qualitative analysis was used to identify major themes among youths' open-ended responses. ResultsIn all, 469 youth (mean age 18.8 years; female: 299/469, 63.8%; White race: 332/468, 70.8%) responded. On average, respondents obtained their first phone at 12.2 years of age. Most participants (325/459, 71.1%) stated they received their first phone out of necessity rather than for entertainment or social reasons. Youth recommended that early adolescents receive their first phone between 12 and 13 years of age primarily for reasons of necessity (146/448, 32.6%). ConclusionsAccording to the participants, phones supported safety and independence by allowing communication with parents and participation in activities. Youth-serving professionals and parents can incorporate these youth perspectives into shared decision-making about phone ownership among families. This can include discussions about essential features, safety, or phone use, as well as maturity and responsibility milestones, which were all key considerations reported by participants in the survey.